Abdominoperineal Resection for Rectal Cancer: Is the Pelvic Drain Externalization Site an Independent Risk Factor for Perineal Wound Healing?. (7th May 2012) - Pramateftakis, M. G.; Raptis, D.; Kanellos, D.; Christoforidis, E.; Tsoulfas, G.; Kanellos, I.; Lazaridis, Ch.
Abstract : Aim . The aim of this paper is to investigate if the insertion of the pelvic drainage tube via the perineal wound could be considered as an independent risk factor for perineal healing disorders, after abdominoperineal resection for rectal malignancy. Patients and Methods . The last two decades, 75 patients underwent elective abdominoperineal resection for malignancy. In 42 patients (56%), the pelvic drain catheter was inserted through the perineal wound (PW group), while in the remaining 33 (44%) through a puncture skin wound of the perineum (SW group). Patients' data with respect to age (P = 0.136 ), stage (P > 0.05 ), sex (P = 0.188 ) and comorbidity (P = 0.128 ) were similar in both groups. 25 patients ( PW versus SW : 8 versus 17, P = 0.0026 ) underwent neoadjuvant radio/chemotherapy. Results . The overall morbidity rate was 36%, but a significant increase was revealed in PW group (52.4% versus 9%, P = 0.0007 ). In 33.3% of the patients in the PW group, perineal healing was delayed, while in the SW group, no delay was noted. Perineal healing disorders were revealed as the main source of increased morbidity in this group. Conclusion . The insertion of the pelvic drain tube through the perineal wound should be considered as an independent risk factor predisposing to perineal healing disorders.